1988
DOI: 10.1007/bf00205442
|View full text |Cite
|
Sign up to set email alerts
|

Importance of MHC antigen expression on solid tumors in the in vitro interaction with autologous blood lymphocytes

Abstract: In 54 patients with lung and 14 with ovarian carcinomas the quantitative variations of the major histocompatibility complex (MHC)-determined class I and class II antigens of the tumor cells were related to their in vitro interaction with blood lymphocytes, to the lymphoid infiltration of the tumors, and to the metastatic state of the disease. The tumor cell-lymphocyte interaction was measured by the proliferative response in mixed lymphocyte tumor cell culture and by the cytotoxic activity of the lymphocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…In PTC, the presence of autoantibodies to cytokeratin 1 therefore suggests the development of an autoimmune response, which infers Th-cell activation. (Topalian, 1994;Vanky and Klein, 1991). The finding of cytokeratin 1 antibodies in HT but not GD serum corroborates a cytolytic mechanism in PTC and HT, producing autoantibodies primarily to intracellular antigens.…”
Section: Discussionsupporting
confidence: 67%
“…In PTC, the presence of autoantibodies to cytokeratin 1 therefore suggests the development of an autoimmune response, which infers Th-cell activation. (Topalian, 1994;Vanky and Klein, 1991). The finding of cytokeratin 1 antibodies in HT but not GD serum corroborates a cytolytic mechanism in PTC and HT, producing autoantibodies primarily to intracellular antigens.…”
Section: Discussionsupporting
confidence: 67%
“…The majority of cytotoxic T lymphocytes (CTL) recognize tumor cells in association with class I molecules encoded by the MHC. Several types of tumor cells either do not express, or display greatly reduced levels of class I MHC antigens on their surface [1,20,29,30]. It was shown that expression of class I molecules can be induced on the surface of different tumor cells by IFN and TNFc~ treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of tumors with different tissue origins lack or express only low levels of class I antigens. Thus, they may not be able to induce an effective immune response [1,28,29]. It was shown recently that treatment of tumor cells with interferon (IFN) and tumor necrosis factor (x (TNFc0 induced the expression of MHC class I antigens on tumor cells [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series of experiments human tumours that lacked or had low amounts of MHC class I antigens were not lysed by, and did not stimulate the autologous blood lymphocytes. Tumours that were recognized in vitro by the lymphocytes expressed both class I antigens and the intercellular adhesion molecule I (ICAM-I) [24][25][26].Offprint requests to: E Vänky, Department of Tumor Biology, Karolinska Institute, 104 01 Stockholm 60500, Sweden Detailed analysis of HLA allele expression on tumour cells is not possible with the conventional lymphocyte typing method. The use of monoclonal antibodies (mAbs) on tissue sections has revealed selective loss of certain alleles [12,13,20].…”
mentioning
confidence: 99%